Alginate hydrogel polymers enable efficient delivery of a vascular-targeted AAV vector into aortic tissue - Remes, Anca; Basha, Dima Ibrahim; Pühler, Thomas; Borowski, Christopher; Hille, Susanne; Kummer, Laura; Wagner, Andreas H.; Hecker, Markus; Soethoff, Jasmin; Lutter, Georg; Frank, Derk; Arif, Rawa; et al. (Molecular therapy. Methods & clinical development, 2021)
Gene therapeutic approaches to aortic diseases require efficient vectors and delivery systems for transduction of endothelial cells (ECs) and smooth muscle cells (SMCs). Here, we developed a novel strategy to efficiently deliver a previously described vascular-specific adeno-associated viral (AAV) vector to the abdominal aorta by application of alginate hydrogels. To efficiently transduce ECs and SMCs, we used AAV9 vectors with a modified capsid (AAV9SLR) encoding enhanced green fluorescent protein (EGFP), as wild-type AAV vectors do not transduce ECs and SMCs well. AAV9SLR vectors were embedded into a solution containing sodium alginate and polymerized into hydrogels. Gels were surgically implanted around the adventitia of the infrarenal abdominal aorta of adult mice. Three weeks after surgery, an almost complete transduction of both the endothelium and tunica media adjacent to the gel was demonstrated in tissue sections. Hydrogel-mediated delivery resulted in induction of neutralizing antibodies but did not cause inflammatory responses in serum or the aortic wall. To further determine the translational potential, aortic tissue from patients was embedded ex vivo into AAV9SLR-containing hydrogel, and efficient transduction could be confirmed. These findings demonstrate that alginate hydrogel harboring a vascular-targeting AAV9SLR vector allows efficient local transduction of the aortic wall.